2018
DOI: 10.1038/s41598-017-18905-7
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic localisation of SRF coactivators, MKL1 and MKL2, and their role in dendritic spine morphology

Abstract: The megakaryoblastic leukaemia (MKL) family are serum response factor (SRF) coactivators, which are highly expressed in the brain. Accordingly, MKL plays important roles in dendritic morphology, neuronal migration, and brain development. Further, nucleotide substitutions in the MKL1 and MKL2 genes are found in patients with schizophrenia and autism spectrum disorder, respectively. Thus, studies on the precise synaptic localisation and function of MKL in neurons are warranted. In this study, we generated and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…Previously, we reported the generation and evaluation of antibodies against MKL1 and MKL2 (Kaneda et al . ). Our western blotting revealed that the anti‐MKL1 antibody does not recognize MKL2, and the anti‐MKL2 antibody does not recognize MKL1 (Kaneda et al .…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Previously, we reported the generation and evaluation of antibodies against MKL1 and MKL2 (Kaneda et al . ). Our western blotting revealed that the anti‐MKL1 antibody does not recognize MKL2, and the anti‐MKL2 antibody does not recognize MKL1 (Kaneda et al .…”
Section: Resultsmentioning
confidence: 97%
“…Our western blotting revealed that the anti‐MKL1 antibody does not recognize MKL2, and the anti‐MKL2 antibody does not recognize MKL1 (Kaneda et al . ). In addition, according to full blot images, other major extra bands were not detected (Supplementary information, Kaneda et al .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations